4. Polityka w zakresie równości płci i pozycja kobiety we współczesnym Kirgistanie .......... 227 - Tomków, Barbara (Kirgistan – oblicza transformacji, 2020)
EQUALITY POLICY AND THE STATUS OF WOMEN IN MODERN KYRGYZSTANThe work on the situation of women in Kyrgyzstan raises issues related to the period of transformation after the collapse of the Soviet Union. The text presents legislative changes regulating women’s rights. Another issue is social awareness of inequalities and thus the participation of women in social and political life. Part of the work is devoted to describing the practice of bride kidnapping. The paper also covers other traditional elements such as traditional role of the woman as a leader and religious guide. An important emphasis is placed on labour migration, its realities and its impact on the situation of women.